Dinâmica ambiental do mercado do peixe do portinho e suas implicações para a saúde – São Luís, Maranhão - SANTOS , Geiziane Oliveira Gomes (2021)
The environmental health in public markets and fairs affects not only the products that are sold there but the health of their workers and consumers. In this research, we aimed to discuss the environmental health of the Fish Market of Portinho of São Luís/MA through its spatial dynamics, its distribution, its trade dynamic, and the factors of prevalence for their sanitary historic. The Fish Market of Portinho is known as a commercial complex of two markets (Internal and External), and one of the biggest centers of fish commercialization and distribution in the state of Maranhão. This is a qualitative study that used a descriptive, explanatory and case study approach, included in the universe of iconographic and participatory methods as well. For data collection, a Field Research Protocol was developed that included the aspects of the Covid-19 pandemic. Secondary data were obtained through documentary research. For primary data, interviews were conducted with the market managers and government representatives, surveys were applied with market workers and photography was used for iconographic investigation. The spatial data analysis was performed using geoprocessing tools, and content analysis for qualitative data. It was identified mostly male workers (80%) who have between 11 and 40 years of work in the market. The Mercado do Peixe continues to have economic relevance and commercialize various fish species that come from different regions of Brazil. The cleaning conditions of the market were perceived by most traders as “bad”, they described unequally water supply distribution and also informed some restrictions for toilet access. To 80% of the workers, there is an association between fish handling and health, and 70% of them informed that the Market’s environmental conditions could affect their health. In October 2020, around half of the workers were infected with Covid-19 (47%) and approximately 30% continued to work in the Market even with flu-like symptoms during the pandemic. The main challenges reported by the workers were: lack of a proper structure for fish commercialization, absence of government, lack of environmental education campaigns, flood by tide, insecurity, and a dirty environment. In this way, we concluded that the problems related to the Market environmental dynamics represent significant health risks to workers and the commercialized fish. Among the prevalence factors for the market hygienic and sanitary conditions, it is highlighted the lack of recognition of the External Market as part of the Fish Market of Portinho from their workers and responsible government agencies, making it vulnerable to health risks that may emerge. This study demonstrates how public markets could become an environment of spreading diseases such as Covid-19. In this way, this research brings the voices and perceptions of the workers in an effort to create a dialogue with the government agencies about the need to establish closer relations between the Market and to reinforce the urgency to execute structural interventions for it. Furthermore, this study represented a great opportunity for the university to get closer to its surrounding social dynamics, as this market, with economic, social, health, and cultural relevance to the city of São Luís and the state of Maranhão.